Predikitor Niat Terhadap Kepatuhan Perilaku Minum Obat Pada Penderita TB Paru di Poli Paru RSUD Kota Kendari - Nur Ramadhan; Narmawan; Hasrima Hasrima (Jurnal Kesehatan Masyarakat Celebes, 2022)
Pulmonary tuberculosis occupies the second position in the world with the most cases because in some places treatment services are less accessible to some people in peripheral areas and cause treatment to be incomplete or partly to stop treatment because they cannot stand the side effects of drugs. Non-compliance begins with a lack of intention to take treatment. In the basic concept of the theory of behavior (theory of planned behavior), the aim is to determine the relationship between attitudes, subjective norms and behavioral control on the intention to take medication for pulmonary tuberculosis patients at the Pulmonary Polyclinic, Kendari City Hospital. This type of research is quantitative with a correlational design through a cross sectional approach. The research sample was 32 respondents aged 17 to 65 years. The study was taken using accidental sampling technique. The research instrument uses an attitude scale to intention, a subjective norm scale to intention, and a behavioral control scale to intention. The data analysis technique is using rank spearmen correlation analysis using computerization. The results of the study of attitudes towards medication adherence intentions obtained a correlation coefficient of 0.246 which has a significance value of 0.175, indicating that there is no relationship. Subjective norm on intention to take medication adherence obtained a correlation coefficient of 0.518 which has a significance value of 0.002 indicating there is a relationship. Behavioral control towards medication adherence intention obtained a correlation coefficient of 0.273 with a significance value of 0.130 indicating no relationship. So it can be concluded that the attitude variable and behavioral control on medication adherence have no relationship, and the subjective norm variable has a relationship.